Synthesis of Amino Terminal Clicked dendrimers. Approaches to the application as a biomarker - Molina, Noemí; Nájera-Albendín, Francisco; Guadix-Domínguez, Juan Antonio; perez-pomarez, Jose M; Vida-Pol, Yolanda; Perez-Inestrosa, Ezequiel (ACS Publications, 2019)
Herein, we present an easy and efficient synthesis of amino terminal dendrons, combining protection/deprotection reactions with copper-catalyzed azide alkyne cycloaddition in a convergent way. This new approach affords dendrons in gram scale with excellent yields and easy purification. By choosing the appropriate azido-functionalized core, these dendrons lead to a more efficient and controlled convergent synthesis of dendrimers with different sizes and shapes and multivalence. The amino terminal dendrimers were analyzed by diffusion-ordered spectroscopy experiments. The observed dendrimer size is in excellent correlation with the expected size and shape by molecular dynamic simulations. The construction of these kinds of nanostructures, in a simple and efficient way, opens new opportunities for biomedical applications. Moreover, by choosing the appropriate core, these versatile macromolecules become an excellent fluorescent biomarker.
Keywords: Marcadores bioquímicos; Azides; Dendrons; Mixtures; Molecules; Solvents